A green-electrospun nanofibrous scaffold incorporating polyethylenimine-modified liposomes for sustained BMP2 gene delivery and enhanced osteogenic differentiation - Zhang, Lin; Chen, Mengxia; Chen, Zhen; Chen, Sunfei; Duan, Shenghan; Lou, Shuqi; Wang, Hongsheng (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionBone tissue engineering requires scaffolds that mimic the native extracellular matrix and provide sustained delivery of osteoinductive factors. This study focuses on developing a multifunctional scaffold using a green electrospinning process to combine the biocompatibility of silk fibroin (SF) with a non‐viral gene delivery system for sustained expression of Bone Morphogenetic Protein 2 (BMP2).MethodsA green electrospinning technique, using an aqueous SF and polyethylene oxide (PEO) solution, was employed to fabricate nanofibrous scaffolds, eliminating the use of harsh organic solvents. Polyethylenimine (PEI) modified liposomes (LipoPEI) were used to encapsulate a BMP2‐encoding plasmid (pDNABmp2). These gene‐loaded nanoparticles were incorporated into the SF‐PEO nanofibers. The resulting scaffolds were characterized for morphology (SEM), structure (FTIR, XRD), and drug release kinetics. Biological performance was evaluated by assessing cell viability (MTT assay), cell attachment (SEM), gene transfection efficiency (confocal microscopy), and osteogenic differentiation (alkaline phosphatase (ALP) activity, Alizarin Red S staining) using bone marrow mesenchymal stem cells (BMSCs).ResultsPhysicochemical characterization confirmed the successful formation of uniform pDNABmp2@LipoPEI nanocomplexes with a particle size of approximately 266 nm and a positive surface charge of +16.9 mV. These nanocomplexes were homogeneously incorporated into smooth, bead-free SF‐PEO nanofibers with average diameters ranging from 460 to 541 nm. The composite scaffold demonstrated a highly sustained release of pDNABmp2 over 14 days. In vitro studies using rat bone marrow-derived mesenchymal stem cells (BMSCs) revealed that the scaffold possesses excellent biocompatibility, promoting robust cell adhesion, spreading, and proliferation. Furthermore, the gene‐loaded scaffold successfully mediated the transfection of BMSCs, leading to significant upregulation of osteogenic markers, including alkaline phosphatase (ALP) activity and extensive calcium mineral deposition over 21 days.DiscussionThe novel composite scaffold combines the structural advantages of SF with a sustained BMP2 gene delivery system, showing remarkable potential to promote osteogenic differentiation. This work presents a promising, environmentally friendly, and effective platform for bone tissue engineering and regenerative medicine.